Etude in silico de l'inhibition de l'enzyme Acétylcholinestérase - ترشة أسماء – صخر خديجة (university of eloued جامعة الوادي, 2024)
من خلال هذه الدراسة, تطرقنا إلى إنزيم AChE, مستهدف علاجي لمرض الزهايمر، من خلال تثبيط وظيفته الإنزيمية والمتمثلة في تكسير الناقل العصبي الأسيتيل كولين في الجسم. باستخدام طرق النمذجة الجزيئية، وتحديدًا تقنية الالتحام الجزيئي (Molecular docking), قمنا بدراسة أنماط التفاعل الموجودة ما بين إنزيم AChE و ثمانية مثبطات فلافونيدية "flavonoids" مكتشفة مؤخرا ,ومقارنتها بمثبط Galantamine , المستعمل في علاج المراحل الخفيفة والمتوسطة من مرض الزهايمر بداية من الخمسينات الى يومنا هذا. استخدم في هذا العمل برنامج Molegro Virtual Docker و برنامج Autodockالذي تم تقييم مدى كفاءتهما من خلال حساب انحراف الجذر التربيعي (RMSD) للمعقد المدروسDX61, حيث وجدنا أن قيم RMSD اقل من A°2, مما يدل على مصداقية هذا البرنامج. حسب نتائج الالتحام , تبين ارتباط المثبطات المدروسة داخل الفجوة الرئيسية لإنزيم AChE مع اختلاف في التموضع نظر لخصوصية شكل الفجوة ,و استقرار هذه المثبطات داخل الموقع الفعال ناتج عن تشكل روابط هيدروجينية ,العديد من التفاعلات الكارهة للماء, وتفاعلات فاندر فالس, مع الأحماض الامينية الرئيسية. اعتمادا على نظرية الكثافة الوظيفية DFT بقاعدة B3LYP/6-311G/++/d/p تم تحديد المعايير الكمومية الخاصة بهذه المثبطات بهدف دراسة الترابط بين الفعالية التثبيطية للمركبات المدروسة و البنى الجزيئية وأخيرا تم التنبؤ بالحركية الدوائية ((ADME للمثبطات المدروسة من خلال دراسة خاصية التشبه بالأدوية "druglikeness" و كذلك التنبؤ باحتمالية الامتصاص المعوي (HIA) و النفاذية عبر الحاجز الدموي الدماغي (BBB ) Through this study, we addressed the enzyme AChE, a therapeutic target for Alzheimer's disease, by inhibiting its enzymatic function of breaking down the neurotransmitter acetylcholine in the body. Using molecular modeling methods, specifically molecular docking, we studied the interaction patterns between the AChE enzyme and eight recently discovered flavonoid inhibitors, and compared them to the inhibitor Galantamine, which was used to treat mild and moderate stages of Alzheimer's disease since01950s to present day. In this work, Molegro Virtual Docker and Autodock were used, the efficiency of which was evaluated by calculating the root mean square deviation (RMSD) of the studied complex DX61, where we found that the RMSD values ​​are less than 2A°, which indicates the reliability of this program. According to the docking results, it was shown that the studied inhibitors bind within the main cavity of the AChE enzyme with a difference in position due to the specificity of the cavity shape, and the stability of these inhibitors inside the active site results from the formation of hydrogen bonds, many hydrophobic interactions, and van der Waals interactions, with the main amino acids. Based on density functional theory (DFT) with the rule B3LYP/6-311G/++/d/p, the quantitative standards for these inhibitors were determined with the aim of studying the correlation between the inhibitory effectiveness of the studied compounds and their molecular structures. Finally, the pharmacokinetics (ADME) of the studied inhibitors was predicted by studying the “druglikeness” property, as well as predicting the potential for intestinal absorption (HIA) and permeability across the blood-brain barrier (BBB)
مدكرة ماستر كيمياء
Keywords: لالتحام الجزيئي; مثبطات DFT; Autodock; MDV; AChE; .; molecular docking; DFT inhibitors